O nowelizacji po drugiej stronie Odry. Zmiana Ustawy Zasadniczej Republiki Federalnej Niemiec z 20 grudnia 2024 r. .......... 145 - Kowalski, Rafał S. (Współczesne zmiany konstytucji w wybranych państwach europejskich: Pomiędzy partykularyzmem prawnym a wspólnotą doświadczeń, 2025)
ON THE AMENDMENT ACROSS THE ODER: AMENDMENT TO THE BASIC LAW OF THE FEDERAL REPUBLIC OF GERMANY OF DECEMBER 20, 2024At the end of 2024, another amendment to the Basic Law of the Federal Republic of Germany was adopted. It concerned the regulations relating to the Federal Constitutional Court – a constitutional court based on the Kelsenian model and a crucial constitutional body of the Federal Republic of Germany. The article proposes that there is a correlation between the Polish constitutional court crisis and the amendment discussed. The paper examines the significance of the Federal Constitutional Court for the German constitutional system, the legal situation before and after the amendment, as well as the political context of the changes and the reactions to them. The crisis surrounding the Polish Constitutional Tribunal is also discussed briefly in order to identify the parallels between the amendment in Germany and the constitutional situation in Poland. The article explains the essence of the amendment and the point of the correlation between it and the constitutional situation in Poland.